2000
DOI: 10.1073/pnas.200367597
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular unesterified arachidonic acid signals apoptosis

Abstract: Cyclooxygenase-2 (COX-2) is up-regulated in many cancers and is a rate-limiting step in colon carcinogenesis. Nonsteroidal antiinflammatory drugs, which inhibit COX-2, prevent colon cancer and cause apoptosis. The mechanism for this response is not clear, but it might result from an accumulation of the substrate, arachidonic acid, an absence of a prostaglandin product, or diversion of the substrate into another pathway. We found that colon adenocarcinomas overexpress another arachidonic acid-utilizing enzyme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
294
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(314 citation statements)
references
References 35 publications
17
294
0
3
Order By: Relevance
“…Among them, ACS members are candidate molecules to induce cancer-selective cell death (Cao et al, 2000;. Our present data indicate the critical function of ACSL5 in glioma cell survival and suggest that this enzyme could be a rational therapeutic target.…”
Section: Other Factors Affected By Acsl5supporting
confidence: 52%
See 1 more Smart Citation
“…Among them, ACS members are candidate molecules to induce cancer-selective cell death (Cao et al, 2000;. Our present data indicate the critical function of ACSL5 in glioma cell survival and suggest that this enzyme could be a rational therapeutic target.…”
Section: Other Factors Affected By Acsl5supporting
confidence: 52%
“…This reaction is a critical step in several lipid metabolic pathways, including phospholipid biosynthesis, lipid modification of cellular proteins and b-oxidation (Coleman et al, 2002). ACSs are overexpressed in a variety of cancers (Cao et al, 2000(Cao et al, , 2001Yamashita et al, 2000;Sung et al, 2003Sung et al, , 2007Gassler et al, 2005;Liang et al, 2005;Yeh et al, 2006). Moreover, our recent screening identified an ACS inhibitor as a tumorselective inducer of apoptosis Mashima and Tsuruo, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Selective COX-2 inhibition has been shown to induce apoptosis through a cytochrome C-dependent pathway in oesophageal cancer cells (Li et al, 2001). Arachidonic acid, the substrate for COX, stimulates apoptosis, thus enhanced COX-2 expression could inhibit apoptosis by decreasing arachidonic acid (Cao et al, 2000). We found that in vivo, COX inhibition increased apoptosis with no change in proliferation in the primary tumours relative to control.…”
Section: Experimental Therapeuticsmentioning
confidence: 64%
“…Only the SGF diet was associated with a reduction in the development of the nodules which could be related to the interaction between C 20 : 5n-3 and C 20 : 3n-6 (dihomo-GLA) which appear to synergistically control the metabolism of C 20 : 4n-6 and also serve as substrates for less potent prostanoid metabolites, such as PGE 3 and E 1 respectively. This control over C 20 : 4n-6 metabolism by the C 20 : 5n-3/C 18 : 3n-6 (GLA) dietary combination has important implications for the regulation of transcription factors and genes involved in signalling pathways affecting cell proliferation and apoptosis which can influence the development of hepatocyte nodules (41,43) .…”
Section: Modulation Of Rat Hepatocyte Nodulesmentioning
confidence: 99%